Impressionism - Howard, Michael (London Carlton Book Ltd, 1997)
This comprehensive guide to one of the most innovative movements in the history of western art takes the reader from the movement's origins in the 1850s, through its development as demonstrated in the eight Impressionist exhibitions of the 1870s and 1880s and the emergence of the post-Impressionists at the end of the century.
Include Color Illustration and Index
Keywords: Impressionism (Art) -- Painting, French -- Painting, Modern